Indumentária e visualidade: modos de vestir de mulheres Kalunga sob uma perspectiva histórica (séculos XIX e XXI) - Cabral, Alliny Maia Siqueira de Carvalho (2019)
This dissertation discusses historically built meanings through the observation of black women's ways of dressing in the nineteenth century's Brazil and of Kalunga's women ways of dressing in the 21st century. We have started from the observation of photographs of women from the rural black Kalunga community, located in northeastern Goiás, that allow a perception of visual approximation between the construction of these women's clothing and that of black women portrayed in nineteenth-century images in Brazil. The adopted methodology includes photographs analysis and fieldwork, developed in the Kalunga community. To support the proposed discussion, the research comprehends an interdisciplinary approach, moving amongst the studies referring to Fashion and Clothing; Material Culture and Visual Culture. During the research, we noticed the importance of images for the study of clothing, through which it was possible to trace relations between fashion, tradition, and sociability. Based on reports from women in the Kalunga community, we could understand how their relationship with clothing is plural and heterogeneous, and should not, therefore, be simply categorized but rather problematized. The collected reports marked themes about the feeling of resistance related to historical social inequality, belonging to the community and ways of dressing as an important instrument to deal with these issues.